What is the matter with newsroom culture? A sociomaterial analysis of professional knowledge creation in the newsroom. (April 2018) - Steensen, Steen
This article presents a study of what affects professional knowledge creation when journalism students have their periods of internship in legacy, yet highly digitized newsrooms. A total of 16 Norwegian j-students are interviewed and 30 internship reports analysed in order to detect the different actors – both humans and non-humans – that matter when students learn through practice in such newsrooms. Through this analysis, this article aims at understanding some of the tensions between legacy and digital culture that many newsrooms today are marked by and how these tensions affect professional knowledge creations for the journalists of tomorrow. The study is framed by sociomaterial perspectives on learning and journalistic practice and argues that two types of materiality are especially important for j-students' professional knowledge creation during periods of internship: the structure and layout of the newsroom and the software applications in use at the newsroom.